Analisis Komoditas Unggulan Sektor Pertanian di Kabupaten Solok - Elfi Afriani; Muhammad Irfan (Universitas Negeri Padang, 2023)
This study aims to analyze the agricultural sector base growth and development of the agricultural sector compared to other sectors. Which is the agricultural sub-sector, the development of the progress of sector growth, the agricultural sub-sector of Solok Regency, which is the leading commodity of the agricultural sector of Solok Regency, how is the distribution and center of agricultural superior production in Solok Regency which consists of 14 districts. This study uses secondary data, namely the production data of each agricultural commodity in 2016-2020 obtained from the Central Bureau of Statistics of Solok Regency. The results showed that there were 5 commodities that became superior commodities that had basic, specialization and competitive aspects in Solok Regency, namely clove commodities (plantations), bananas (horticulture), roses, cattle (animal husbandry) and in the lake (fishery) with each commodities have both a sectoral contribution aspect and a higher growth aspect at the district level compared to the provincial level.